Potential of phenolic compounds in persimmon fruit extract (Diospyros Kaki L.) against atherosclerosis in rats - Alhara Yuwanda; Endang Hanani; Fadhlina Chani Saputri (Universitas Ahmad Dahlan, 2019)
Persimmon fruits (Diospyros kaki L.) contain catechins and epigallocatechin gallate (EGCG) which have antioxidant properties. The study aimed to prove the antioxidant potential of phenolics in persimmon fruit (D. kaki L.) in reducing oxidation of LDL and as antiatherosclerotics. The research method included an anti-oxidant test using a UV-VIS spectrophotometer and measurement of polyphenol level using High-Performance Liquid Chromatography (HPLC). Also, blood serum levels were examined in vitro and in vivo based on the histopathology of the aorta of male Sprague-Dawley rats subjected to a cholesterol diet. There were five test groups: positive control (receiving Î±-tocopherol), negative control, dose I (administered with the extract at 450 mg/kg BW), dose II (extract 900 mg/kg BW), and dose III (extract 1800 mg/kg BW). The testing was carried out for eight weeks. Antioxidant test using DPPH method produced an IC50 of 44.07Â±15.06 mg/mL. The polyphenol contents identified in the persimmon extract were catechins 2.55% and EGCG 9.49%. The results showed that the persimmon extract exhibited antioxidant activity that prevented atherosclerosis through the mechanism of LDL oxidation. At a concentration of 1,800 mg/kg BW, the extract decreased the aortic wall thickness by 31.20% and showed activities that were not significantly different from the positive control (p value= 0.05).